Frontiers and hotspots evolution in anti-inflammatory studies for coronary heart disease: A bibliometric analysis of 1990–2022 - Zhang, Jiale; Ji, Chenyang; Zhai, Xu; Tong, Hongxuan; Hu, Jingqing (Frontiers in Cardiovascular Medicine, 2023)
Background: Coronary heart disease (CHD) is characterized by forming of arterial plaques composed mainly of lipids, calcium, and inflammatory cells. These plaques narrow the lumen of the coronary artery, leading to episodic or persistent angina. Atherosclerosis is not just a lipid deposition disease but an inflammatory process with a high-specificity cellular and molecular response. Anti-inflammatory treatment for CHD is a promising therapy; several recent clinical studies (CANTOS, COCOLT, and LoDoCo2) provide therapeutic directions. However, bibliometric analysis data on anti-inflammatory conditions in CHD are lacking. This study aims to provide a comprehensive visual perspective on the anti-inflammatory research in CHD and will contribute to further research. Materials and Methods: All the data were collected from the Web of Science Core Collection (WoSCC) database. We used the Web of Science's systematic tool to analyze the year of countries/regions, organizations, publications, authors, and citations. CiteSpace and VOSviewer were used to construct visual bibliometric networks to reveal the current status and emerging hotspot trends for anti-inflammatory intervention in CHD. Results: 5,818 papers published from 1990-2022 were included. The number of publications has been on the rise since 2003. Libby Peter is the most prolific author in the field. "Circulation" was ranked first in the number of journals. The United States has contributed the most to the number of publications. The Harvard University System is the most published organization. The top 5 clusters of keywords co-occurrence are inflammation, C-reactive protein, coronary heart disease, nonsteroidal anti-inflammatory, and myocardial infarction. The top 5 literature citation topics are chronic inflammatory diseases, cardiovascular risk; systematic review, statin therapy; high-density lipoprotein. In the past two years, the strongest keyword reference burst is "Nlrp3 inflammasome", and the strongest citation burst is "Ridker PM, 2017 (95.12)". Conclusions: This study analyzes the research hotspots, frontiers, and development trends of anti-inflammatory applications in CHD, which is of great significance for future studies.